Nuclear disarmament regional perspectives on progress - Kamath, P. M. (Contributions to conflict management, peace economics and development ;, 2013)
This volume presents a range of views on the current state of global nuclear disarmament from eminent scholars from India, Israel and France. Chapters present and analyse the relationships between India, Pakistan and the USA, Russia and the USA, the position of the EU and of Israel. The perspectives presented range from optimism to pessimism on global nuclear disarmament and consequences for human security.